Identification of hepatitis a virus antibody among Bangladeshi children and their correlation with socioeconomic condition (Northern International Medical College Journal, 2015)
Background : Hepatitis A virus infection is endemic in many developing countries including Bangladesh. Children infected with Hepatitis-A virus typically have asymptomatic disease.Objective : To observe the anti-HAV positivity in children & to determine any relation between anti-HAV positivity & socioeconomic condition.Materials & Methods : A cross sectional observational study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital & Dhaka Shishu (Children) Hospital (DSH) from July 2008 to June 2009. Serum samples from 254 children aged between 1-15 years were tested for antibody (IgM & IgG) against hepatitis A virus (HAV) and detailed history was taken to find out the associated risk factors like residence, family income, source of drinking water, sanitation facility etc.Results : Hepatitis A virus antibody was positive in 141 (55.5%) of 254 children. Among all children anti-HAV positivity was significantly higher (p=0.004) in lower income group (64.8%) than higher income group (47.0%). Anti-HAV positivity was significantly higher (93.8%) in non-sanitary latrine users & in those who used unsafe drinking water.(p=0.006)Conclusions : Majority of children were found sero-positive against HAV by 15 year of age. Anti-HAV positivity was significantly higher in lower socioeconomic group.Northern International Medical College Journal Vol.6(1) 2014: 12-14